Drug utilization of corticosteroid in post-operative cataract patients at Klinik Mata Utama (KMU) Madura - Solihah, Riyadatus; Rahmadani, Rizal Umar; Puspitasari, Dianita Rahayu (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2023)
A cataract is contributed to 51% of blindness in the world. Cataract surgery is needed to restore the normal eye function. Therapeutic management post cataract operative is generally carried out 1-4 weeks by administering antibiotics, corticosteroids or NSAIDs by oral or topical routes. Corticosteroids administration increase intraocular pressure (IOP), therefore should be taken into account in post-operative cataract. The aim of this study was to observe the pattern of corticosteroid use in post-cataract surgery patients at the Klinik Mata Utama (KMU) Madura. Observational retrospective research involved 153 patients who consumed corticosteroids during their post operative cataract period. The results showed that 122 patients (79.7%) received combination therapy of topical dexamethasone and oral methylprednisolone, while 31 (20.3%) received combination therapy of topical dexamethasone and oral prednisone. 140 Patients (91,6%) showed good recovery with corticosteroids, and 13 patients (8,4%) experienced the IOP as a side effect of topical corticosteroids. In conclusion, the corticosteroids therapy for post-operative cataract patients should be managed properly to prevent the side effects of increasing IOP.